Lexical semantics, syntax, and event structure - Hovav, Malka Rappaport; Doron, Edit.; Sichel, Ivy. (Oxford : Oxford University Press, 2010)
This text focuses on the linguistic representation of temporality in the verbal domain and its interaction with the syntax and semantics of verbs, arguments, and modifiers. It explores the division of labour between syntax, compositional semantics, and lexical semantics in the encoding of event structure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Semantics; Grammar, Comparative and general -- Temporal constructions